Pharmacosomes: In Targeted Drug Delivery System - Abhishek Yadav,; Mohd Amaan,; Adarsh Dubey,; Dheeraj Kushwaha, (Asian Journal of Pharmaceutical Research and Development, 2024)
Pharmacosomes are a cutting-edge method of medication delivery based on a lipid transport system. A novel approach to drug delivery called "drug targeting" seeks to deliver the medication to the intended site of action or absorption while preventing any other non-target site from being exposed to it. Drug targeting is a practical delivery method that allows medicinal agents to be delivered to a particular location without endangering other organs. Pharmacosomes are colloidal drug dispersions that are hexagonally assembled into micelles, vesicles, or nanometric- size micelles that are covalently attached to the phospholipid. They function pretty accurately as appropriate carriers for drug administration because of their unique characteristics, which include small size, amphiphilicity, active drug loading, high entrapment efficiency, and stability. This paper focous on about the Pharmacosomes, there advantages, disadvantages, and matters that are needed for the formulation, and there characterization and also application.